Nonlinearity of ocean heat uptake during warming and cooling in the FAMOUS climate model. Issue 7 (3rd April 2015) - Bouttes, N.; Good, P.; Gregory, J. M.; Lowe, J. A.
Abstract Atmospheric CO2 concentration is expected to continue rising in the coming decades, but natural or artificial processes may eventually reduce it. We show that, in the FAMOUS atmosphere‐ocean general circulation model, the reduction of ocean heat content as radiative forcing decreases is greater than would be expected from a linear model simulation of the response to the applied forcings. We relate this effect to the behavior of the Atlantic meridional overturning circulation (AMOC): the ocean cools more efficiently with a strong AMOC. The AMOC weakens as CO2 rises, then strengthens as CO2 declines, but temporarily overshoots its original strength. This nonlinearity comes mainly from the accumulated advection of salt into the North Atlantic, which gives the system a longer memory. This implies that changes observed in response to different CO2 scenarios or from different initial states, such as from past changes, may not be a reliable basis for making projections.